Struktur Komunitas Ikan di Danau Serantangan Kelurahan Sagatani Kecamatan Singkawang Selatan Kota Singkawang - Riski Kurnianto; Ahmad Mulyadi Sirojul; Inpurwanto Inpurwanto (Fakultas Pertanian Universitas Tanjungpura, 2020)
Serantangan lake has an area of ± 258 Ha, the condition of this lake is horrible because there had been from unlicensed gold mining activities in the area, causing many changes ranging from the color of the waters, depth to the number of fish caught. This study was conducted to determine the composition, uniformity, and diversity of fish and plankton species as well as the dominant fish species in Serantangan Lake. This research was conducted for 3 months at Lake Serantang using a purposive sampling method, namely by going directly to the waters of Serantangan Lake to install fishing gear (1.5-inch trawlers, traps and scoops) from station 1 to station 5. Based on the results of the study fish caught during the study were included in 12 species and 7 families. Diversity index is 2,74; the uniformity index value is 0.96; the dominance index value is 0.07.